Implementation of Problem Based Learning Models to Improve Learning Outcomes of Plant and Animal Cell Structures - Kusmiyati, Kusmiyati; Wibawa, I Made Ari; Mulyanthi, Dewi Iryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Various learning problems teachers face in schools must be solved with alternative solutions supporting 21st-century learning, which develops student-centered learning and provides a problem-solving experience in the real world. The Problem-Based Learning (PBL) model was chosen as a solution, providing the broadest possible experience for students to think critically, creatively, collaboratively, and communicatively. This research aims to improve learning outcomes of plant and animal cell structures through a problem-based learning model. Data was collected in two SMAN 1 Kerambitan class XI MIPA meetings, totalling 27 people. Cognitive learning outcomes are taken at the end of the meeting, while affective and psychomotor learning outcomes are taken during the learning process. The learning results are then subjected to qualitative analysis to determine learning completeness. The scores obtained by students are compared with the minimum completeness criteria that apply in 70 schools. Cognitive learning results at the first meeting show an average score of 74 for the number of students. Twenty-four people completed it, and three did not, while at the second meeting, the average score was 82, and all students completed it. It can be concluded that implementing the PBL model can improve the learning outcomes of plant and animal cell structures.